The Air Freight Transport at Spanish Airports: Towards Selective Concentration and Internationalization - López-Escolano, Carlos; Cruz-Alonso, Daniel; Pueyo-Campos, Ángel (Revista de Estudios Andaluces, 2019)
The process of globalization requires that local and regional actors must be incorporated into global economic networks and flows to achieve competitiveness and economic development. This implies changes that modify the impacts and scope of transport infrastructures. In the case of freight distribution, air transport is still a little part of international cargo volume, where only a few airports centralize most of this volume. In Spain, only four airports are relevant in the management of air cargo, especially for the international freight management. This research characterizes the main patterns of air cargo in Spanish airports. To achieve this goal, they are analyzed the recent evolution and patterns of air cargo transport around different variables, finding some notable changes that are modifying the air hierarchy.